A Study On: Electric Power Line Networking For A Smart Home - Kr. Thakur, Ajay (International Journal of Psychosocial Rehabilitation, 2020)
Electrical power line networking is a home networking system that can interconnect computers within the smart home. This uses thrilling power outlets and AC wiring to relay data around a home or small office. It is based upon the ’no new wires’ concept. Power line communications is a fairly new telecoms area. PLC uses full-duplex methods to transmit data through power lines as the medium for transmitting electrical signals over a grid. For advanced meter reading, home control, and street lighting, PLC systems are used. Several PLC technologies, listed according to their operating frequency range, are explored in this paper. Power line networking uses power line communications (PLC) to connect computers using existing home power outlets, turning any electrical outlet in the building effectively into a network connection. Power line networking is one of home networking’s cheapest types and has low start-up costs and minimal IT workload. Power line networks can transmit phone calls and faxes as well as Internet services over regular electrical wiring.